The Existence Of The Tana Luwu Traditional Game Among The Millennials As A National Cultural Heritage - Rafli Alamsyah; Hadi Pajarianto; Muhammad Irham Zainuri (JUARA : Jurnal Olahraga, 2023)
Traditional games are part of the nation's rich and varied cultural heritage, including the conventional games of Tana Luwu. However, with the development of technology and modern lifestyles, traditional games among millennials in Tana Luwu are being threatened. Therefore, this study aims to analyze the Tana Luwu traditional game among millennials as a national cultural heritage. This study used a quantitative descriptive method with data collection techniques through interviews and observation. The results show that the level of recognition of traditional games is still quite good; some are even known by 90% of the respondents. At the same time, the frequency of young people playing these traditional games is the highest played by young people at 54%. Therefore, more severe and sustainable efforts are still needed to strengthen the Tana Luwu traditional game among millennials as part of the nation's cultural heritage. This can be done through education, development, and appropriate technology to facilitate access and promote the traditional game of Tana Luwu to millennials. The results of this research can contribute to preserving the conventional Tana Luwu game as a national cultural heritage among millennials and using the right technology to facilitate access and promote the traditional game of Tana Luwu to millennials. The results of this research can contribute to preserving the conventional Tana Luwu game as a national cultural heritage among millennials and using the right technology to facilitate access and promote the traditional game of Tana Luwu to millennials. The results of this research can contribute to preserving the conventional Tana Luwu game as a national cultural heritage among millennials.